2022
DOI: 10.3389/fphar.2022.990461
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of roles of lysyl oxidases in the predictions of prognosis, chemotherapy and immunotherapy in glioma

Abstract: Background: Previous investigations have illustrated that lysyl oxidase family enzymes (LOXs) are contributing factors for tumor progression and remodeling immunomicroenvironment. However, it is scarce regarding comprehensive analysis of LOXs in the predictions of prognosis, chemotherapy and immunotherapy in glioma, the highly invasive brain tumor. Our present work aimed to explore the prognostic value, chemotherapeutic drug sensitivity and immunotherapy according to distinct LOXs expressions in glioma through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…A poor prognosis was found for GBM patients with high Lox expression in the TCGA cohort ( P = 0.044) but not in the CGGA cohort ( P = 0.067). These results were partially consistent with those of previous studies ( Han et al, 2014 ; Huang et al, 2018 ; Patnam et al, 2022 ; Xia et al, 2022 ). They reported the independent prognostic role of Lox in lower-grade glioma, suggesting that the prognostic value of Lox is related to the grade of glioma.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A poor prognosis was found for GBM patients with high Lox expression in the TCGA cohort ( P = 0.044) but not in the CGGA cohort ( P = 0.067). These results were partially consistent with those of previous studies ( Han et al, 2014 ; Huang et al, 2018 ; Patnam et al, 2022 ; Xia et al, 2022 ). They reported the independent prognostic role of Lox in lower-grade glioma, suggesting that the prognostic value of Lox is related to the grade of glioma.…”
Section: Discussionsupporting
confidence: 93%
“…The expression of Loxl1 is significantly related to the antiapoptotic effects and migration of glioma cells ( Li et al, 2018 ; Yu et al, 2020 ). Consistent with our results, previous studies have indicated a similar prognostic role for Loxl1 in glioma using a single Kaplan‒Meier analysis ( Xia et al, 2022 ; Yu et al, 2020 ). In this study, we further included more clinicopathological factors and performed further Cox regression analyses in multiple GBM cohorts.…”
Section: Discussionsupporting
confidence: 93%
“…As mentioned before, ECM stiffness and structural organization are strongly regulated by the activity of LOX enzyme family, which includes LOX and LOX-like (LOXL) 1-4 ( 23 ). Due to their involvement in different processes, as linking bi-directionally the ECM and acting directly on the activation of signaling pathways regulating cancer cell survival, proliferation and differentiation, LOXs have been identified as pivotal factors in the formation and progression of different tumor types as glioma, gastric and endometrial carcinoma ( 130 133 ). Among the LOX family of enzymes, LOXL3 has also been shown to play immunomodulatory functions in the TME.…”
Section: Resultsmentioning
confidence: 99%
“…LOX expression was associated with lymph node metastasis, distant tumor metastasis and poor prognosis in GC patients, and the integrated analysis supported LOX as a speci c diagnostic and prognostic biomarker for GC patients (Jia et al 2022). In addition, LOX has an excellent predictive value for chemotherapy, immunotherapy and prognosis in patients with glioma (Xia et al 2022). Few studies are available concerning LOX in ccRCC.…”
Section: Discussionmentioning
confidence: 99%